Divided We Rule: Influencer Polarization on Twitter During Political Crises in India - Dash, Saloni; Mishra, Dibyendu; Shekhawat, Gazal; Pal, Joyojeet (Proceedings of the International AAAI Conference on Web and Social Media, 2022)
Influencers are key to the nature and networks of information propagation on social media. Influencers are particularly important in political discourse through their engagement with issues, and may derive their legitimacy either solely or partly through online operation, or have an offline sphere of expertise such as entertainers, journalists etc. To quantify influencers' political engagement and polarity, we use Google's Universal Sentence Encoder (USE) to encode the tweets of 6k influencers and 26k Indian politicians during political crises in India. We then obtain aggregate vector representations of the influencers based on their tweet embeddings, which alongside retweet graphs help compute the stance and polarity of these influencers with respect to the political issues. We find that while on COVID-19 there is a confluence of influencers on the side of the government, on three other contentious issues around citizenship, Kashmir's statehood, and farmers' protests, it is mainly government-aligned fan accounts that amplify the incumbent's positions. We propose that this method offers insight into the political schisms in present-day India, but also offers a means to study influencers and polarization in other contexts.